(untitled) (Journal of Universal Science Research, 2025)
As we know, time is one of the most crucial aspects of our lives which helps us organize everything step by step. Without time, it would be impossible to define a day, a week, a year, or even life itself. Time is indeed fundamental to human existence. It allows us to measure change, plan for the future and make sense of the past. Everything from the rotation of the Earth (which gives us days) to its orbit around the Sun (which defines a year) is governed by time. In science, time is considered one of the basic dimensions of the universe and in daily life, it is essential for scheduling, goal setting and progress.